A Hypergeometric Integral with Applications to the Fundamental Solution of Laplace's Equation on Hyperspheres - Chapling, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We consider Poisson's equation on the n-dimensional sphere in the situation where the inhomogeneous term has zero integral. Using a number of classical and modern hypergeometric identities, we integrate this equation to produce the form of the fundamental solutions for any number of dimensions in terms of generalised hypergeometric functions, with different closed forms for even and odd-dimensional cases.